Peningkatan Kemampuan Menentukan Unsur Intrinsik Cerita Pendek Melalui Model Pembelajaran Kooperatif Tipe Think Pair Share - Noveri Amal Jaya Harefa; Dernipika Zai (Universitas Nias, 2023)
This study aims to improve students' ability to determine the intrinsic elements of short stories using the Think Pair Share Learning Model in class XI-IIS 2 SMA Negeri 1 Gido. The implementation procedure: planning, action, observation, and reflection. The research results obtained were: (1) students' ability to determine the intrinsic elements of short stories in cycle I, namely the lowest score was 60 and the highest score was 80 with an average score of 69.5 while cycle II obtained the lowest score 75 and the highest score 90 with an average score 80.7; (2) student activity in the first cycle of the first meeting of students who were active 40.7%, and the second meeting of active students 59.1% while in the second cycle the first meeting of active students was 69.4% and the second meeting of active students 88.5 %; (3) the activity of researchers in the first cycle of the first meeting was 47.05% and the second meeting was 68.05% while in the second cycle the first meeting was 79% and the second meeting was 95%. From these data it can be concluded that by applying the think pair share cooperative learning model it can improve students' abilities in determining the intrinsic elements of short stories